Error control for hp-adaptive approximations of semi-definite eigenvalue problems - Giani, Stefano; Grubišić, Luka; Ovall, Jeffrey (Elsevier, 2012)
We present reliable a-posteriori error estimates for hp-adaptive finite element approximations of semi-definite eigenvalue/eigenvector problems. Our model problems are motivated by the applications in photonic crystal eigenvalue computations. We present detailed numerical experiments confirming our theory and give several benchmark results which could serve the purpose of numerical testing of other adaptive procedures.